Pendidikan dan Pekerjaan Ibu terhadap Pemberian ASI - Pipitcahyani, Tatarini Ika (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2017)
Abstract: This study aims to determine the relationship between education and mother's work tobreastfeeding. The research design used was analytic with a population of 17 mothers who had a 6-month-old baby. Sampling used is total sampling. The research instrument used questionnaire sheet.Data were analyzed using Fisher Test. Results obtained from 17 respondents ie 10 mothers (58.8%) gaveExclusive breastfeeding and 7 mothers (41.2%) did not give Exclusive Breast Milk. Based on the resultsof the results provided exclusive breastfeeding based on mother's education is the SMA as many as 5people (50%) and the results given ASI Exclusive based on the mother's work is the IRT as many as 6people (60%). Result of statistical test with Fisher Test result value (p) value 1.0 for education relationwith value of ASI and value (p) value 0,270 for job relation with breastfeeding with error level 0,05result> 0,05 then hypothesis accepted book not there is a significant relationship between the Educationand the mother's work on the Exclusive Asi award.